-2(-6a-4)-2=-90

Simple and best practice solution for -2(-6a-4)-2=-90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(-6a-4)-2=-90 equation:


Simplifying
-2(-6a + -4) + -2 = -90

Reorder the terms:
-2(-4 + -6a) + -2 = -90
(-4 * -2 + -6a * -2) + -2 = -90
(8 + 12a) + -2 = -90

Reorder the terms:
8 + -2 + 12a = -90

Combine like terms: 8 + -2 = 6
6 + 12a = -90

Solving
6 + 12a = -90

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 12a = -90 + -6

Combine like terms: 6 + -6 = 0
0 + 12a = -90 + -6
12a = -90 + -6

Combine like terms: -90 + -6 = -96
12a = -96

Divide each side by '12'.
a = -8

Simplifying
a = -8

See similar equations:

| 8z-72=8 | | 6x^5+17x^4-x^2+3x+3=0 | | 6+4x=-4x+22 | | 4(x-2)=-3(5-x) | | 5x+2x-8=41 | | Z^2=8-8i | | 5x-6+3=7 | | 5x+2x-8=42 | | 15x=17+8x-24 | | -19=13x+2 | | 6c+3+11=8c | | 45x+60x+185y=10500 | | 0.5y+9=31 | | 3.96=-44z | | X+(-5)=18 | | 0.5y+9= | | -2.5x-1.7=-16.4 | | 3x+2(x+7)=86 | | 3x-5-x+2=13 | | 8.5=4x+5 | | X+(-4)=-25 | | 2x-5=64 | | -4t+24=16 | | 49x+1=48x+3 | | 2.86-21.1= | | (-18)=5x-8 | | 2r-r=9 | | =-3/7x-1/7 | | 5(0)=15+3y | | x+6=-5(x+6) | | 9a-18= | | 4*y-8=3*y+12 |

Equations solver categories